Organizações Sociais e a Educação Pública: entre a parceria e a privatização - Silva, Juliana Cristine Brandão (2019)
This work aimed to investigate the process of implementation of shared management between public authorities and social organizations in the educational sphere and, more specifically, the research sought to verify at which historical moment and from which ideology, such partnerships became possible in the country. To this end, bibliographic studies were needed to understand under what circumstances the process of educational decentralization was proposed for Latin America, and from when services under the responsibility of public authorities began to be managed by the third sector, and its multiple social organizations. This process, also called publicization, designates the transfer of competencies from the public-state to the public-non-state sphere and can be understood as a radical form of decentralization. Based on this research, the results indicate that such a process became possible in Brazil after the Managerial Reform of the State Apparatus, during the government of Fernando Henrique Cardoso (1995-2003), who invested in the systematization and deepening of neoliberal policies in Brazil, policies that were systematized in the Washington Consensus, which basically consisted of a list of recommendations to Latin American countries that were willing to reform their economic systems.